PERFORMANCE INDICATORS IN PROFICIENCY TEST EXERCISES - Waheed, S.; Rahman, A.; Siddique, N.; Zaidi, J. H.; Ahmad, S. (The Nucleus, 2020)
Normalized performance for individual participating laboratories in a proficiency test exercise for the determination of radionuclides in mushroom reference material were assigned through three quality indicators. Relative bias, z- scores and u-test scores were calculated for the data on 134Cs, 137Cs and 40K submitted by laboratories representing six different countries. Data received for these radionuclides were statistically evaluated to obtain consensus mean values of 4.4 Bq/kg, 2899 Bq/kg and 1136 Bq/kg for 134Cs, 137Cs and 40K respectively at a confidence intervals (at a significance level of 0.05). The target values for the standard deviation (Ïƒ) calculated for this exercise are 18.9%, 6.9%, 9.9% for 134Cs, 137Cs and 40K, respectively, and have been assigned on the basis of the reproducibility standard deviation. Due to the small data sets for each radionuclide the limiting value for the u-test parameter was taken as 1.95 to determine if a result passes the test.